Histopathological study of nasal masses, a one year retrospective study in a tertiary care centre of Assam - Alam, Nurul; Ahmed, S. K. Abdullah; Deka, Monoj K.; Sheikh, Shah Alam (International Journal of Research in Medical Sciences, 2021)
Background: Prolapsed lining of the nasal sinuses are defined as nasal polyp. Diseases of the nasal cavity include viral, bacterial and fungal infections, nasal cavity tumors (benign and malignant) as well as inflammations of the nasal mucosa. This study was undertaken to note the various histopathological patterns of nasal masses, their classification and relative distribution of various lesions with regard to age and sex in our setting. Methods: The study is done for a period of 1 year (July 2018 to June 2019). In this study, 30 patients are selected who presented in our hospital with nasal masses and having multiple types of clinical presentations. Results: Total 30 cases presented as nasal mass. Overall male to female ratio was 2.3:1. Nonneoplastic nasal masses formed the largest group of lesions; 24 cases (80%), followed by 6 cases (20%) of neoplastic nasal masses. Inflammatory polyp was the commonest non neoplastic lesion constituting 22 cases followed by rhinosporidiosis with 2 cases. Out of the 6 neoplastic nasal masses, 5 were benign and 1 was malignant. Out of the benign neoplastic masses, inverted papilloma constituted 3 cases and nasopharyngeal angiofibroma constituted 2 cases. Malignant neoplastic mass was embryonal rhabdomyosarcoma. Conclusions: Nasal obstruction and rhinorrhea are the most common symptoms of presentation. Simple inflammatory nasal polyps are the most common histological pattern seen in our environment, and surgery is the best modality of treatment.